A Reflection on the Relation Between Mortgage Contract and the Agreement of Pledge of Security; A Critical Study about the Evolution of the Pledged Assets from the Traditional Pawn to the Pledge in Modern Law - Jamshid Jafarpour; Saeed Siahbidi Kermanshahi (آموزه‌‌های فقه مدني, 2021)
The historical studies shows that Imamiyah jurists have not thought that there is no difference between mortgage (Arabic: رهن rahn) and pawn but they have defined rahn as loan collateral. But with the consideration of the limits of mortgage contract in our legal system and the impossibility of applying rahn for some assets or promises, some authors have tried by presenting new theories to deal with these limits. One of these theories is the dualities of mortgage contract and pledge. If it is possible to confirm two characteristics “having particular name and specific conditions and decrees” in law for the agreement of the pledge it can be resulted that the mentioned contract is of nominate contracts. The study of the present laws show that the conclusion of the agreement in the form of the mortgage contract is not possible in most cases because of the absence of one of conditions. The legislator has used the term ”وثیقة“ (pawn). These rules can be applied from two sides: first they prove that it has legal base and it has used several times in different rules. Second the legislator has used the term ”وثیقة“ (pawn) in the cases which one of the provisions of the conclusion of the agreement is not and he has refused to apply the term ”رهن“ (mortgage) through this, he has created a modern foundation (establishment) in the legal system.